Effect of light curing modes and ethanol immersion media on the susceptibility of a microhybrid composite resin to staining - Flávio Henrique Baggio Aguiar; Thalita Regina Vieira e Oliveira; Débora Alves Nunes Leite Lima; Luis Alexandre Maffei Sartini Paulillo; José Roberto Lovadino (University of São Paulo, 2007)
The aim of this in vitro study was to evaluate the susceptibility of a hybrid composite resin (Filtek Z250 - 3M ESPE) to staining, when light cured in four different modes and immersed in two different media. Composite resin specimens were randomly prepared and polymerized according to the experimental groups (conventional - 550 mW/cm² / 30 seconds; soft start - 300mW/cm² / 10 seconds + 550 mW/cm² / 20 seconds; high intensity - 1060 mW/cm² - 10 seconds; pulse delay - 550 mW/cm² - 1 seconds + 60 seconds of waiting time + 550 mW/cm² - 20 seconds) and immersed in one of two media (distilled water or absolute ethanol) for 24h. Next, the specimens were immersed in a 2% methylene blue solution for 12 hours. Afterwards, the specimens were washed and prepared for the spectrophotometric analysis. For statistical analysis, two-way ANOVA (4X2) and Tukey's test were performed on the data at 0.05 confidence level. Soft start showed the least staining, and was statistically different from the high intensity and pulse delay light curing modes (p<0.05). Conventional light curing unit did not show statistically significant differences from any other groups (p>0.05). There were no significant differences between the two immersion media (p>0.05). The soft start polymerization mode showed lower susceptibly of the composite resin to staining than high intensity and pulse delay, irrespective of the immersion medium.